Uzbekistan quality job creation as a cornerstone for sustainable economic growth. - Anderson, Kym (Asian Development Bank, 2020)
This book analyses how Uzbekistan can boost sustainable economic growth to create more and better job.It considers how the country can consolidate achievements from recent policy reforms and maintain reform efforts to accelerate sustainable growth. Policy recommendations cover fostering macroeconomic stability, increasing investment in physical infrastructure, enhancing human capital, improving firms access to finance, and lowering barriers to international trade and foreign investment inflows.